2021
DOI: 10.1128/msphere.00244-21
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of SARS-CoV-2 in an Immunocompromised Patient with Non-Hodgkin Lymphoma

Abstract: Tracking the within-patient evolution of SARS-CoV-2 is key to understanding how this pandemic virus shapes its genome toward immune evasion and survival. In the present study, by monitoring a long-term COVID-19 immunocompromised patient, we observed the concurrent emergence of mutations potentially associated with immune evasion and/or enhanced transmission, mostly targeting the SARS-CoV-2 key host-interacting protein and antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 22 publications
9
57
0
Order By: Relevance
“…Incomplete coverage with the vaccine leads to infection of immunocompromised persons who are likely to harbor the virus for prolonged periods (or chronically), allowing for mutations that are then selected for immune evasion and better fitness to the human host. 1 The new variants are sufficiently altered structurally such that neither prior SARS-CoV-2 infection or even much higher levels of vaccine-induced antibodies are protective.In this issue of JAMA, Spitzer and colleagues assess the effect of a booster dose of the mRNA vaccine BNT162b2 (Pfizer-BioNTech) on acquisition of SARS-CoV-2 infection among health care workers in a tertiary medical center in Tel Aviv, Israel. 2 Israel achieved high vaccination coverage of most health care workers, who were prioritized for immunization receiving both doses of the BNT162b2 vaccine by the end of January 2021.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incomplete coverage with the vaccine leads to infection of immunocompromised persons who are likely to harbor the virus for prolonged periods (or chronically), allowing for mutations that are then selected for immune evasion and better fitness to the human host. 1 The new variants are sufficiently altered structurally such that neither prior SARS-CoV-2 infection or even much higher levels of vaccine-induced antibodies are protective.In this issue of JAMA, Spitzer and colleagues assess the effect of a booster dose of the mRNA vaccine BNT162b2 (Pfizer-BioNTech) on acquisition of SARS-CoV-2 infection among health care workers in a tertiary medical center in Tel Aviv, Israel. 2 Israel achieved high vaccination coverage of most health care workers, who were prioritized for immunization receiving both doses of the BNT162b2 vaccine by the end of January 2021.…”
mentioning
confidence: 99%
“…Incomplete coverage with the vaccine leads to infection of immunocompromised persons who are likely to harbor the virus for prolonged periods (or chronically), allowing for mutations that are then selected for immune evasion and better fitness to the human host. 1 The new variants are sufficiently altered structurally such that neither prior SARS-CoV-2 infection or even much higher levels of vaccine-induced antibodies are protective.…”
mentioning
confidence: 99%
“…The mutation is located in close proximity to residue 144, which is deleted in the Alpha variant. A 141-144 deletion has also been reported in several chronically SARS-CoV-2 infected immunocompromised individuals 20 . Furthermore, a 143-145 deletion is also observed in the Omicron variant 21 .…”
Section: Introductionmentioning
confidence: 92%
“…More and more studies appear where the ability to mutate the SARS-CoV-2 virus is analyzed in immunocompromised patients such as lymphomas 15,16 . Moreover, in this study carried out by Siqueira et al 17 , the authors concluded that cancer patients had a greater capacity to develop SARS-CoV-2 variants, with four globally dominant SARS-CoV-2 haplotypes (C241T, C3037T, C14408T and A23403G) as the majority of consensus sequences analyzed.…”
Section: Sars-cov-2 Variants and Cancer Patientsmentioning
confidence: 99%